Occupational Therapists’ Experiences and Perspectives About Using Apps in Neurorehabilitation in India: A Qualitative Study Protocol - Kashish Surana; Pramod D. Lambor; Shashank Mehrotra (MethodsX)
Mobile apps are increasingly used in healthcare and are transforming neurorehabilitation by supporting patient care and enhancing clinical practice. Apps have demonstrated significant potential for supporting patients with various neurological disorders. Occupational therapists play a crucial role in integrating apps to enhance patients' performance by selecting those that match their needs. Existing research highlights the potential of therapy-specific apps in occupational therapy to meet the patient’s unique needs. Most existing studies have been conducted in Western countries, and the experiences and perspectives of occupational therapists about using apps, their adoption, and implementation in Indian occupational therapy practice remain unexplored. The study aims to explore the experiences and perspectives of occupational therapists about the use of apps for neurorehabilitation in India. Occupational therapists who are working with patients having any neurological disorders in India will be recruited for this study. Braun and Clarke's approach to thematic analysis will be used to explore occupational therapists' experiences, investigated through an in-depth interview using a semi-structured interview guide.